The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41598-020-78749-6
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol droplet-size distribution and airborne nicotine portioning in particle and gas phases emitted by electronic cigarettes

Abstract: The reliable characterization of particle size distribution and nicotine delivery emitted by electronic cigarettes (ECs) is a critical issue in their design. Indeed, a better understanding of how nicotine is delivered as an aerosol with an appropriate aerodynamic size is a necessary step toward obtaining a well-designed nicotine transfer from the respiratory tract to the bloodstream to better satisfy craving and improve smoking cessation rates. To study these two factors, recent models of EC devices and a dedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…The increase in metal concentration with power can be attributed to a general increase in aerosol particle concentrations, which has also been shown to be temperature-dependent. 58,59 At higher powers, there is a faster increase in the filament's temperature, vaporizing a high volume of the EC liquid, thus generating a high concentration of particulates in aerosols. However, a marginal increase in metal emissions was observed when the power was increased from 25 to 45 W, suggesting that most of the power below 25 W has been used to evaporate the EC liquid.…”
Section: Effects Of Ec Power Puff Duration and Devicementioning
confidence: 99%
“…The increase in metal concentration with power can be attributed to a general increase in aerosol particle concentrations, which has also been shown to be temperature-dependent. 58,59 At higher powers, there is a faster increase in the filament's temperature, vaporizing a high volume of the EC liquid, thus generating a high concentration of particulates in aerosols. However, a marginal increase in metal emissions was observed when the power was increased from 25 to 45 W, suggesting that most of the power below 25 W has been used to evaporate the EC liquid.…”
Section: Effects Of Ec Power Puff Duration and Devicementioning
confidence: 99%
“…Many scholars have carried out in-depth research on the atomization characteristics of nozzles by analyzing the size and distribution of atomized particles from the viewpoints of both numerical and experimental evaluation. Factors affecting the atomization effect such as the gas, liquid flow, liquid temperature, and viscosity have been extensively experimentally evaluated in the literature [ 3 , 4 , 5 , 6 , 7 ]. For instance, Wang et al [ 6 ] studied the pressure swirl and air flow of an atomizer with experiments in which the droplet size and distribution under different fuel pressure were measured using a laser particle-size analyzer.…”
Section: Introductionmentioning
confidence: 99%
“…While the cannabis industry and regulators have focused on testing the concentrate oils in vaporizers, they have done minimal testing on the actual aerosol mixtures produced by these devices. E-cigarette aerosols are known to be a combination of liquid droplet particles and gas-phase molecules. The aerosols from vaped cannabis products are also thought to be a combination of small oil droplets and vaporized gas-phase molecules but have not been well-characterized. However, some studies have shown low-molecular-weight compounds do exist in the gas phase, and it is known that compounds with higher molecular weights (similar to that of cannabinoids) when heated to a high temperature can create critical supersaturation, leading to nucleation and small particle formation .…”
Section: Introductionmentioning
confidence: 99%